Institutional Legacies and "Sticky Layers": What Happens in Cases of Transformative Policy Change?. Issue 3 (March 2019) - Carey, Gemma; Kay, Adrian; Nevile, Ann
Policy layering has received significant scholarly attention in recent years as a means to explain and understand the outcomes of policy implementation efforts, particularly within the context of incremental change. However, little is known about how processes of policy layering and institutional legacies play out in (relatively rare) system-wide and transformative policy reforms. This article presents a critical case study of one such reform—the Australian National Disability Insurance Scheme (NDIS). In examining the implementation experiences of the NDIS, we resist the bifurcation of the study of policy dynamics into a stability versus big bang dualism by revealing that many influential and constraining factors in a layering process are common across both incremental and transformative reforms. Moreover, we find that layering is not merely an unfortunate by-product of previous institutional structures but a tool that is actively sought and used by policy makers to tackle implementation challenges that, once set in motion, can move beyond the ability of policy makers to control.